Liver disease in pregnancy - Shashank Shekhar; Gaurav Diddi (Elsevier, 2015)
Deranged liver function tests are encountered in 3% of pregnancies. The potential causes are classified as those unique to and those just incidental to pregnancy. Pregnancy-related diseases are the most frequent causes of liver dysfunction during pregnancy and exhibit a trimester-specific occurrence during pregnancy. Differentiation of liver dysfunction as that related to and just incidental to pregnancy is the key to management, especially when liver dysfunction is encountered after 28 weeks of pregnancy. It can be judged from the fact that delivery remains the cornerstone of management of pregnancy-related diseases except hyperemesis gravidarum. This is an overview of the causes of liver dysfunction during pregnancy; an update on the underlying mechanisms of their occurrence, especially liver diseases unique to pregnancy; and a methodological approach to their diagnosis and management.